Pengaruh Gender, Penghargaan Finansial dan Pertimbangan Pasar Kerja Terhadap Minat Berkarir Menjadi Akuntan Publik pada Mahasiswa Akuntansi Sekolah Tinggi Ilmu Ekonomi Balikpapan - Fice Handayani (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2021)
This study aims to prove whether gender, financial rewards and labor market considerations affect career interest in becoming a public accountant for accounting students at the Balikpapan College of Economics.The analytical tool used in this research is Multiple Linear Regression. Financial rewards and labor market considerations affect career interest in becoming a public accountant for accounting students at the Balikpapan College of Economics, and among the two variables the most dominant is financial rewards with a higher tcount value. greater than the value of t table (2.908> 1.992). and the sig value. 0.005 <0.05. For the gender variable, it shows that there is no influence on the interest in a career as a public accountant for accounting students at the Balikpapan College of Economics, where the results show that tcount (-1.199) is smaller than t table (1.992) with a sig value. 0.234 is greater than the specified significance of 0.05. Keywords: Gender, Financial Rewards, Labor Market Considerations, Career Interest to Become A Public Accountant